2021
DOI: 10.36547/nbc.1118
|View full text |Cite
|
Sign up to set email alerts
|

Callus formation, phenolics content and related antioxidant activities in tissue culture of a medicinal plant colocynth (Citrullus colocynthis)

Abstract: Callus cultures from stems, leaves and roots of colocynth were initiated on MS media supplemented with various combinations of 2,4 dichlorophenoxyacetic acid (2,4-D) with kinetin (KIN) and benzyladenine (BA) with α-naphthaleneacetic acid (NAA). The highest percentage of callus formation frequency (98.9%) was obtained from stem explants grown on MS media supplemented with (1.0 mg/L) 2,4-D + (1.0 mg/L) KIN. The total phenolics and flavonoid content of the colocynth callus cultures were measured. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…Results illustrated in Figure C indicated that as a consequence to PGRs treatments (NAA, TDZ, BAP, NAA + TDZ, and NAA + BAP), the highest TPC levels were detected at 2.5 mg/L NAA (11.56 mg/g DW) followed by 1.0 mg/L TDZ (11.04 mg/g DW), whereas the minimum TPC (0.2 mg/g DW) levels were detected at high concentrations (20.0 mg/L) of BAP. These findings are in harmony with the previously published reports which showed that NAA at a lower concentration results in highest level of TPC in calli of Citrullus colocynthis L . From the observed data, a positive relationship can be drawn between the total phenolic content and biomass accumulation in callus cultures of O. basilicum.…”
Section: Resultssupporting
confidence: 91%
“…Results illustrated in Figure C indicated that as a consequence to PGRs treatments (NAA, TDZ, BAP, NAA + TDZ, and NAA + BAP), the highest TPC levels were detected at 2.5 mg/L NAA (11.56 mg/g DW) followed by 1.0 mg/L TDZ (11.04 mg/g DW), whereas the minimum TPC (0.2 mg/g DW) levels were detected at high concentrations (20.0 mg/L) of BAP. These findings are in harmony with the previously published reports which showed that NAA at a lower concentration results in highest level of TPC in calli of Citrullus colocynthis L . From the observed data, a positive relationship can be drawn between the total phenolic content and biomass accumulation in callus cultures of O. basilicum.…”
Section: Resultssupporting
confidence: 91%
“…Generally, in DPPH free radical scavenging assay, the extracts demonstrated strong antioxidant activity comparable to that of normal ascorbic acid. Te results are consistent with those of El-Baz et al [12], who found that the extract of Citrullus colocynthis callus had higher DPPH radical scavenging activity than the extract of feld plant leaves. 2 shows the results of the ferricreducing capacities of the extracts.…”
Section: Resultssupporting
confidence: 92%
“…In vitro cultures are promising approaches for the bioprospection of natural products [11,12]. In the search for alternatives to the biosynthesis of valuable secondary metabolites from plants, biotechnological techniques, particularly plant tissue cultures, have been found to have potential as a companion to conventional agriculture in the industrial production of phytochemical compounds [13].…”
Section: Introductionmentioning
confidence: 99%